MUNTU: AN OUTLINE OF NEO-AFRICAN CULTURE, by Janheinz Jahn. Translated by Marjorie Greene. Faber and Faber, London, 1961. Ill. 30s. - Beatric, John (International Library of African Music, 1961)
pages: 109-110
Keywords: African Music